Analysis of best performances of front crawl swimming: a case study - Buglione, A.; Migliaccio, G. M.; De Siati, F.; Russo, L.; Padulo, J.; Larion, A.; di Prampero, P. E. (Acta Kinesiologica, 2025)
Purpose: The aim of this work was to: 1) measure the energy cost of front crawl swimming at various speeds (range .8 -1.8 m·s-1 in elite and medium level swimmers; in addition, 2) estimate the maximal aerobic power and maximal anaerobic capacity from the relationship between overall energy spent and individual best times over distances from 50m to 1500m in one elite athlete. It will also be shown, that 3) the so obtained values are rather close to the actually measured ones.